Strong-field effects induced in the extreme ultraviolet domain - Makos I.; Orfanos I.; Skantzakis E.; Liontos I.; Tzallas Paraskevas; Forembski A.; Nikolopoulos L. A. A.; Charalambidis Dimitris (2020)
Motivated by the achieved high intensities of novel extreme ultraviolet (XUV) radiation sources, such as free electron lasers and laser-driven high harmonic generation beamlines, we elaborate on their perspective in inducing observable strong field effects. The feasibility of extending such effects from the infrared and visible spectral regimes in the XUV domain is supported through numerically calculated models of near-future experiments. We highlight the advancement of performing studies in the time domain, using ultra-short XUV pulses, which allows for the temporal evolution of such effects to be followed. Experimental and theoretical obstacles and limitations are further discussed. © The Author(s), 2020. Published by Cambridge University Press in association with Chinese Laser Press.
Keywords: Fizikai tudományok